Lessons learned from the first wave of aging with HIV. - Justice, Amy C; Braithwaite, R Scott (AIDS (London, England), 2012)
In this perspective piece, the authors consider what has been learned and is being studied about aging with HIV in resource-rich settings. The authors argue that although there is much that will be different about aging with HIV in other parts of the globe, there are common themes and approaches to care. These include the observation that most patients have more than one health condition, and the need to assess individual risk, prioritize care, and consider the total burden of disease when considering further testing and treatment.
Keywords: Aging; Comorbidity; Health Services Needs and Demand; HIV Seropositivity; Humans; Individualized Medicine; Male; Middle Aged; Polypharmacy; United States